GE_GERICHTE P/23219/2019 vom 30. Januar 2020 - GE Cour de justice (2020)
ENQUÊTE PÉNALE;INFRACTIONS CONTRE L'HONNEUR;RÉPUTATION;RÉSEAU SOCIAL;ENVOI SOUS PLI SIMPLE;NOTIFICATION DE LA DÉCISION | CPP.310.al1.leta; CPP.85.al2; CP.173